Analysis of Political Law and Public Policy on the Issue of BPJS Health Losses in the JKN Program in 2024 - Wiweka, Wiweka; Arifin Hoesein, Zainal (Pascasarjana UDA, 2023)
In 2024, BPJS Health will be in the spotlight regarding the alleged loss of IDR 20 trillion in the JKN Program, due to potential fraud and inconsistencies in fund management. This issue raises questions about the effectiveness of public policy and legal politics in managing BPJS Health as well as supervision of programs that affect public health services. This study aims to analyze the influence of politics, law, and public policies implemented in 2024 on BPJS Health's financial governance, especially related to losses in the JKN program, as well as to find solutions to improve financial management and reduce losses. The research method used is normative juridical, using a legislative approach and an analytical approach. The results show that the imbalance between the receipt of contributions and claim costs, as well as inefficient cross-subsidy policies, are the main causes of losses. Suggested policy solutions include adjustment of contribution rates, improvement of cross-subsidies, strengthening supervision of medical claims, and management based on more accurate data. This study shows the need for more responsive, efficient, and data-based policies to overcome BPJS Health losses, as well as the importance of transparent and accountable management so that the JKN program can run sustainably and provide equal access to health for all Indonesian people.